Picturing Modernity : Highlights from the Photography Collection of the San Francisco Museum of Modern Art. - Nickel, Douglas R.; Ross, David A. (San Francisco : SFMOMA (San Francisco Museum of Modern Art), 1998)
Adams, Ansel ; Adams, Robert ; Adamson, Robert ; Arbus, Diane ; Atget, Eugène ; Atkins, Anna ; Baldessari, John ; Becher, Bernd & Hilla ; Brady, Mathew ; Brassaï ; Cameron, Julia Margaret ; Cartier-Bresson, Henri ; Coplans, John ; Cunningham, Imogen ; DeCarava, Roy ; Disdéri, André Adolphe Eugène ; Evans, Frederick H. ; Evans, Walker ; Fenton, Roger ; Fontcuberta, Joan ; Fox Talbot, William Henry ; Frank, Robert ; Friedlander, Lee ; Gibson, Ralph ; Goldin, Nan ; Groover, Jan ; Gutmann, John ; Hill, David Octavius ; Hine, Lewin ; Jackson, William Henry ; Kertesz, André ; Klein, William ; Kühn, Heinrich ; Lange, Dorothea ; Levine, Sherrie ; Levitt, Helen ; Maar, Dora ; Man Ray ; Matta-Clark, Gordon ; Meatvard, Ralph Eugene ; Model, Lisette ; Moholy-Nagy, Laszlo ; Morell, Abelardo ; Moriyama, Daido ; Morris, Wright ; Nixon, Nicholas ; O'Sullivan, Timothy H. ; Penn, Irving ; Prince, Richard ; Riis, Jacob ; Rodchenko, Alexander ; Ross, Judith Joy ; Salgado, Sebastião ; Sander, August ; Sherman, Cindy ; Siskind, Aaron ; Sommer, Frederick ; Southworth, Albert Sands ; Steichen, Edward J. ; Stieglitz, Alfred ; Strand, Paul ; Sudek, Josef ; Sugimoto Hiroshi ; Teynard, Félix ; Warhol, Andy ; Watkins, Carleton E. ; Weegee ; Weston, Edward ; Winogrand, Garry
biografie
Engels
boek